2021
DOI: 10.3758/s13428-021-01557-x
|View full text |Cite|
|
Sign up to set email alerts
|

Testing the construct validity of competing measurement approaches to probed mind-wandering reports

Abstract: Psychology faces a measurement crisis, and mind-wandering research is not immune. The present study explored the construct validity of probed mind-wandering reports (i.e., reports of task-unrelated thought [TUT]) with a combined experimental and individual-differences approach. We examined laboratory data from over 1000 undergraduates at two U.S. institutions, who responded to one of four different thought-probe types across two cognitive tasks. We asked a fundamental measurement question: Do different probe t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 214 publications
(281 reference statements)
2
76
0
Order By: Relevance
“…It is an open question as to whether individuals can make a binary distinction between these phenomenologies, much less distinguish in more granularity to respond to the question if it were a Likert scale. Following the efforts made by Kane et al (2021), future research should examine whether using a continuous scale to measure freely moving thought offers any benefit compared with dichotomization 6 . Because the superiority of one measurement decision over the other has not been established, we focus on the limitations of having the dynamic thought probe as a single item, rather than the granularity of the scale itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an open question as to whether individuals can make a binary distinction between these phenomenologies, much less distinguish in more granularity to respond to the question if it were a Likert scale. Following the efforts made by Kane et al (2021), future research should examine whether using a continuous scale to measure freely moving thought offers any benefit compared with dichotomization 6 . Because the superiority of one measurement decision over the other has not been established, we focus on the limitations of having the dynamic thought probe as a single item, rather than the granularity of the scale itself.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed data from 225 participants, whereas Alperin et al,analyzed data from 79. 6 Notably, Kane et al (2021) found that using a continuous measure of the perceived depth of a mind wandering episode offered negligible benefit compared with a dichotomous forced-choice response.…”
Section: Open Questionsmentioning
confidence: 99%
“…A recent report from Kane et al, ( 2021 ) reviewed potential confounds to experience sampling and demonstrated that the reliability and validity of experience sampling reports partly depended on how probes asked about TUTs in laboratory settings. In short, they found that responses to probes similar to those used in the current studies could be influenced by participants’ reactions to their performance on in-lab tasks and may be confounded with participants’ confidence in their probe responses.…”
Section: Discussionmentioning
confidence: 99%
“…TUTs were assessed differently in each experiment. Experiment 1 measured TUTs at the end of the lecture via a 1–7 rating scale about the extent of mind wandering; such retrospective ratings, however, are vulnerable to memory and aggregation errors, as well as response biases, that may reduce their validity compared to in-the-moment thought reports (Kane, Smeekens, et al, 2021 ). Experiment 2 measured TUTs in the moment, with an experience-sampling probe inserted into each of the four lecture segments that asked whether subjects were just mind wandering.…”
Section: Effects Of Interpolated Testing and Pretesting On Tutsmentioning
confidence: 99%
“…Pretesting lecture material, either all at once or before each segment, thus appeared to reduce attention failures during learning. But, as in one of the studies showing that interpolated testing reduced mind-wandering (Szpunar, Khan, et al, 2013 ), attention was assessed with a retrospective-report measure of questionable construct validity (Kane, Smeekens, et al, 2021 ).…”
Section: Effects Of Interpolated Testing and Pretesting On Tutsmentioning
confidence: 99%